Implementasi UAV dan ArcGIS untuk Pemetaan 3D Kawasan Hutan Konservasi Ubadari - Nelson Rumui; Deisya Maulida Al Hamid; Syukron Anas (Journal of Applied Computer Science and Technology, 2025)
This study aims to produce a three-dimensional (3D) visualisation model of the Ubadari Conservation Forest Area in Fakfak Regency, West Papua, using Unmanned Aerial Vehicle (UAV) technology and ArcGIS Pro software. Aerial imagery data was collected through photogrammetric missions with calibrated parameters. This elevation model has high accuracy with a Root Mean Square Error (RMSE) value of 0.35 metres, indicating an average vertical deviation of only about 35 cm from the actual elevation value—accurate enough for conservation and advanced mapping applications. Spatial analysis was conducted to map topography, vegetation index (NDVI), land cover classification using the k-means clustering algorithm, as well as zones prone to degradation and potential fires. The results show that more than 15% of the area has a slope of >30%, and around 22.3% of the area is classified as having poor vegetation health. Meanwhile, 23.7% of the area was classified as low vegetation cover. Degradation and fire-prone zones covered 18.5% of the study area, mainly around road access and the edges of the area. These findings contribute to data-based monitoring systems and form an important basis for risk mitigation planning and conservation forest ecosystem preservation.